Performance evaluation of single-mode and multimode fiber in LAN environment - Abdul Rahman, Farah Diyana; Al-Khateeb, Wajdi Fawzi Mohammed; Hassan Abdalla Hashim, Aisha (World Academy of Science, Engineering and Technology, 2007)
—Optical networks are high capacity networks that meet the rapidly growing demand for bandwidth in the terrestrial telecommunications industry. This paper studies and evaluates single- mode and multimode fiber transmission by varying the distance. It focuses on their performance in LAN environment. This is achieved by observing the pulse spreading and attenuation in optical spectrum and eye-diagram that are obtained using OptSim simulator. The behaviors of two modes with different distance of data transmission are studied, evaluated and compared.